A review of the clinical utility of duloxetine in the treatment of diabetic peripheral neuropathic pain - King JB; Schauerhamer MB; Bellows BK (Dove Medical Press, 2015)
Jordan B King, Marisa B Schauerhamer, Brandon K Bellows Pharmacotherapy Outcomes Research Center, University of Utah College of Pharmacy, Salt Lake City, UT, USA Abstract: Diabetes mellitus is a world-wide epidemic with many long-term complications, with neuropathy being the most common. In particular, diabetic peripheral neuropathic pain (DPNP), can be one of the most distressing complications associated with diabetes, leading to decreases in physical and mental quality of life. Despite the availability of many efficient medications, DPNP remains a challenge to treat, and the optimal sequencing of pharmacotherapy remains unknown. Currently, there are only three medications approved by the US Food and Drug Administration specifically for the management of DPNP. Duloxetine (DUL), a selective serotonin-norepinephrine reuptake inhibitor, is one of these. With the goal of optimizing pharmacotherapy use in DPNP population, a review of current literature was conducted, and the clinical utility of DUL described. Along with early clinical trials, recently published observational studies and pharmacoeconomic models may be useful in guiding decision making by clinicians and managed care organizations. In real-world practice settings, DUL is associated with decreased or similar opioid utilization, increased medication adherence, and similar health care costs compared with current standard of care. DUL has consistently been found to be a cost-effective option over short time-horizons. Currently, the long-term cost-effectiveness of DUL is unknown. Evidence derived from randomized clinical trials, real-world observations, and economic models support the use of DUL as a first-line treatment option from the perspective of the patient, clinician, and managed care payer. Keywords: clinical trials, pharmacoeconomic studies, opioid-utilization, health care utilization, pregabalin, tricyclic antidepressants, gabapentin